Transit and decline of the image - Valencia, Luis Fernando (Estudios de Filosofía, 1997)
First, the author sets aside the process in which "image" and "representation" have lost their original meaning in West history. Thence, it has sprung a crisis the author calls «crisis ofrepresentation». lt is defined by: l. The change of the optical status ofimage, 2. The disappearing of any visual paradigm, so that the image will be no more a medium ofmeaning, 3. As a consequence, metaphorical and symbolical functions of image are now non-working, and 4. At last, there has been a saturation of images. From this diagnosis, the author holds that we presently live in a "fractal culture" or "arder o fdespotic representation", whose akin phenomena are the aesthetisation of worlds of life, and the fall of reason and history. On a second stage, the author studies sorne works of Colombian art in the nineties, he takes as the echoes of the «crisis of representation».